2020
DOI: 10.1002/chir.23165
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical studies of infrared signatures of proton‐bound amino acid dimers with homochiral and heterochiral moieties

Abstract: Proton‐bound homochiral and heterochiral dimers, X‐H+‐X, of five amino acids (X = Ser, Ala, Thr, Phe, and Arg) are investigated theoretically using quantum chemical density functional theory (DFT) calculations and molecular dynamics simulations with the aim to unveil diastereomer‐specific mid‐infrared (mid‐IR) absorption bands in the spectral range of 1000 to 1800 cm−1. The theoretical calculations performed in this work imply that all systems, except Ala2H+, have distinct mid‐IR absorption bands in homochiral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
(67 reference statements)
2
9
0
Order By: Relevance
“…On the other hand, a theoretical study was carried out for such protonated dimers for predicting the performability of IRMPD spectroscopy on the chiral differentiation for amino acids. Using density functional theory (DFT) calculations and molecular dynamics simulations, Poline et al studied the infrared characteristics of homochiral and heterochiral protonated amino acid dimers (Ala 2 H + , Ser 2 H + , Thr 2 H + , Phe 2 H + , Arg 2 H + ) [56]. The results predict that these dimers, except Ala 2 H + , have distinct mid-IR absorption bands in homochiral and heterochiral configurations, making them appropriate to be studied with mid-IR photon dissociation spectroscopy.…”
Section: Molecules Of Diastereomersmentioning
confidence: 99%
“…On the other hand, a theoretical study was carried out for such protonated dimers for predicting the performability of IRMPD spectroscopy on the chiral differentiation for amino acids. Using density functional theory (DFT) calculations and molecular dynamics simulations, Poline et al studied the infrared characteristics of homochiral and heterochiral protonated amino acid dimers (Ala 2 H + , Ser 2 H + , Thr 2 H + , Phe 2 H + , Arg 2 H + ) [56]. The results predict that these dimers, except Ala 2 H + , have distinct mid-IR absorption bands in homochiral and heterochiral configurations, making them appropriate to be studied with mid-IR photon dissociation spectroscopy.…”
Section: Molecules Of Diastereomersmentioning
confidence: 99%
“…Investigation of amino acids (AAs) and their oligomers are of interest because of their fundamental role in biology. Protonation of an AA dramatically alters its structure by changing which inter- and intramolecular noncovalent interactions (NCI) to the environment are preferred. Gas-phase proton-bound AA dimers, meaning pairs of AAs with one extra H + , have gained significant interest, both from experimental and theoretical perspectives because they contain the complexity of inter- and intramolecular NCI, despite their small size. This makes them useful model systems for the NCI in proteins.…”
Section: Introductionmentioning
confidence: 99%
“…While chemical intuition and prior experimental structural evidence have been used in some reports, such as in the IR spectroscopic study of (Ser 8 Cl 2 ) 2− [ 33 ] and (HSer 8 ) + [ 23 ], increasingly a global search for suitable structures has been carried out by the laser-mass spectrometry community using some MD simulation program packages, such as Macromodel by Schrödinger [ 34 ] and DFTB+, which utilizes the DFT-based tight binding method [ 35 , 36 ]. For example, Poline et al applied this approach to investigate the IR signature of several homo- and heterochiral protonated amino acid dimers [ 37 ]. We chose to use the conformer-rotamer ensemble sampling tool (CREST), developed by Grimme and co-workers [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, Andersson et al reported minor differences in the IRMPD spectra of the homo- and heterochiral proton-bound Asn dimer [ 61 ], similar to what we observe in terms of the chirality effects in the IRMPD spectra of the four species discussed. Based on their experiment and also a related theoretical study [ 37 ], the authors suggested that to observe chiral differences within the mid-IR region, a sidechain must be involved in the intermolecular interactions. This hypothesis also appears to apply in the simulated IR spectra of several types of the current species.…”
Section: Resultsmentioning
confidence: 99%